Network Pharmacology-Based Approach Uncovers the Mechanism of GuanXinNing Tablet for Treating Thrombus by MAPKs Signal Pathway - Wang, Mu-Lan; Yang, Qin-Qin; Ying, Xu-Hui; Li, Yuan-Yuan; Wu, Yang-Sheng; Shou, Qi-Yang; Ma, Quan-Xin; Zhu, Zi-Wei; Chen, Min-Li (Frontiers in Pharmacology, 2020)
Background GuanXinNing tablet (GXNT), a traditional Chinese patent medicine, has been found to have remarkable antithrombotic effects and can effectively inhibit pro-thrombotic factors in previous studies. However, the mechanism of its antithrombotic effects remains little known. Methods In this study, we first determined and identified the sources of each main compound in GXNT using liquid chromatography-mass spectrometry (LC-MS). Through the approach of network pharmacology, we predicted the action targets of the active components, mapped the target genes related to thrombus, and obtained potential antithrombotic targets for active ingredients. We then performed gene ontology (GO) enrichment analyses and KEGG signaling pathway analyses for the action targets, and constructed networks of active component–target and active component–target–pathway for GXNT. Additionally, we evaluated the pharmacodynamic effects of GXNT on thrombus using the rat thrombus model induced by FeCl3, observed the effects of antiplatelet aggregation via platelet assay, and further verified the results predicted by network pharmacology via Western blot. Results In total, 14 active ingredients were identified in GXNT, and 83 action targets were predicted, 17 of which are antithrombotic targets that potentially participate in processes including response to oxidative stress and positive regulation of blood vessel endothelial cell migration. KEGG pathway analyses revealed that the predicted action targets were involved in multiple signal pathways, such as MAPK, IL-17, and platelet activation. Pharmacodynamics study found that GXNT could significantly reduce the thrombus length and weight, lower platelet aggregation function, and decrease the levels of Fbg and PAI-1. In addition, GXNT could significantly increase 6-keto-PGF1α content and regulate the ratio of TXB2/6-keto-PGF1α, while not having dramatic effects on TXB2. GXNT was also observed to visibly inhibit maximum platelet aggregation. Herein, we further studied the thrombus-related MAPKs signaling pathway and found that GXNT could significantly reduce the phosphorylation levels of p38MAPK, ERK, and JNK proteins in platelet. Conclusions This study revealed the pharmacodynamic material basis of GXNT and its potential multicomponent–multitarget–multipath pharmacological effects, confirmed the antithrombotic effects of GXNT, and showed that its mechanism may be related to inhibiting phosphorylation of p38, ERK, and JNK proteins in MAPKs signaling pathway, partially verifying the results from network pharmacology. The results from this study could provide a theoretical basis for the development and clinical application of GXNT.